Global Africa : into the twenty-first century - Hodgson, Dorothy Louise; Byfield, Judith A. (Judith Ann-Marie) (2017)
"Global Africa will complicate conventional views of Africa as a place of violence, despair and victimhood--a place and space that other people, states, and organizations act on and steal from. Instead, they aim to document some of the significant global connections, circulations, and contributions that African people, ideas, and goods have made in the world--not just in the United States, but in South Asia, Latin America, Europe, and elsewhere. They will showcase new framings of Africa, but will not romanticize the conditions and circumstances in which too many people on the continent currently live. The essays in this volume will amplify those voices that offer complex and insightful explanations, strategies for solutions, and inspiration for the future."--Provided by publisher.
Why global Africa? / Dorothy L. Hodgson and Judith A. Byfield -- Profile-Ibn Khaldoun: the father of the social sciences / Oludamini Ogumaike -- Trade and travel in Africa's global golden age (AD 700-1500) / t Photo essay: Baohan Street, an African community in Guangzhou, China / Michaela Pelican and Li Dong -- r Zakia Salime -- Profile: a conversation with microbiologist, Dr. Sara Eyangoh / Tamara Giles-Vernick -- The politics, perils, and possibilities of epidemics in Africa / Douglas Webb -- Generative technologies from Africa / Ron English -- "Money in your hand": M-PESA and mobile money in Kenya / Dillon Mahoney -- What's in your cell phone? / James H. Smith -- Bioprospecting: moving beyond benefit sharing / Rachel Wynberg -- Of waste and revolutions: environmental legacies of authoritarianism in Tunisia / Siad Darwish -- Profile: Africa calling, a conversation with Mo Ibrahim / Stuart Reid -- From Lesotho to the United Nations: the journey of a gender justice advocate / Keiso Matashane-Marite -- Meschac Gaba: museum of contemporary African art / Kerryn Greenberg -- Africa in Nollywood: Nollywood in Africa / Onookome Okome -- Globalizing African Islam from below: west African Sufi masters in the United States / Cheikh Anta Babou -- Afropolitanism and its discontents / Obadias Ndaba -- Photo essay: Awra Amba, a model "Utopian" community in Ethiopia / Salem Mekuria.
Includes bibliographical references and index.
Keywords: 2000-2099; Globalization -- Africa -- 21st century; National characteristics, African; Diplomatic relations; Economic history; Globalization; National characteristics, African; Politics and government; Social conditions; Globalisierung; Africa -- Economic conditions -- 21st century; Africa -- Social conditions -- 21st century; Africa -- Politics and government -- 21st century; Africa -- Foreign relations -- 21st century; Africa; Afrika